Strenght And Stress Analysis On Helicopter Rotor Blade Grip - Sulaiman, Zularieff Redzwan (Universiti Sains Malaysia, 2019)
The purpose of this thesis is to design, analyze and apply a spacer with a different materials to the unfilled gap of rotor blade grip for an ultra-light helicopter. The unfilled gap of the blade grip has to be occupied by the spacer in order to obtain the highest grip effectiveness towards the rotor blade. The absence of the spacer might be fine for certain length of rotor blade but it would be wasted if the efficiency of the rotor blade grip ability is not fully utilized. Therefore, these empty spaces of the blade grip are better to be filled in by some sort of materials as the fewer the empty space of the blade grip, the better the grip blade towards the rotor blade it will be. For this project, the chosen materials to fill the empty spaces are epoxy, car body filler and aluminium. The objective for these materials to be filled into the non occupied blade grip area are to act as a spacer (support) and making the blade position more rigid and compact. However, different materials has different strength thus producing different amount of blade grip effectiveness. In order to analyze and monitor each of the different materials behavior, a reliable test can be done. Software such as SOLIDWORKS is used because it offers a simulation test. From the simulation test, strength and stress can be analyzed by setting up a specific constraints and pre-conditions. Besides, it is important to verify the simulation analysis which can be obtained by taking the rotor blade tip deflection from the lab experiment and compared together with the simulation displacement results. As a reference, to have a better insight towards the simulation situation, the model has been setup according to cantilever support situation where it is free of external load except for gravitational force. In a nutshell, from the simulation results, it can be observed that aluminium spacer is the best material to enhance the blade grip effectiveness where all of the results are discussed in this thesis.